2020
DOI: 10.1109/access.2020.2970838
|View full text |Cite
|
Sign up to set email alerts
|

K-Means Multi-Verse Optimizer (KMVO) Algorithm to Construct DNA Storage Codes

Abstract: In an era of information explosion, dealing with massive data has become a problem. Since DeoxyriboNucleic Acid (DNA) is a high-density storage medium with long storage endurance, a DNA based storage system is a viable solution. The first consideration of a DNA storage system is the DNA codes, which can avoid non-specific hybridization of DNA strands in the hybridization reaction process by using related constraints, such as Hamming distance constraints, GC-content constraints, and no-runlength constraints. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The authors in [9] described the construction of the constraint code for DNA storage systems, taking into account the maximum repetition length and the balance between AT and GC pairs. An improved algorithm was proposed in [10] to store information more efficiently considering Hamming distance and run-length constraints. The architecture in [11] implemented an efficient coding technique to limit the length of repeated occurrences of the same base that are difficult to sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [9] described the construction of the constraint code for DNA storage systems, taking into account the maximum repetition length and the balance between AT and GC pairs. An improved algorithm was proposed in [10] to store information more efficiently considering Hamming distance and run-length constraints. The architecture in [11] implemented an efficient coding technique to limit the length of repeated occurrences of the same base that are difficult to sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 and table 5 are the maximum number of sets obtained by each algorithm of A RC 4 (n, d) and A GC,RC 4 (n, d, w) respectively. The value range of coding length is [4,13], and the range of distance D is [3, n]. A in each column represents the previous experimental results (the letter in the upper right corner of each result represents the method used, see Table 3 for details), B represents the experimental results of this paper.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…(12,6,6), are far from the existing experimental results, and some results are equal to the previous results, such as A RC 4 (9, 7) = 8. There are also some cases where the number of codes in the new algorithm is larger than that of the existing codes in the range of coding length [4,13]…”
Section: B Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the mean and standard deviation only show the overall performance of an algorithm, while statistical tests consider whether the results are statistically significant. Therefore, we used the non-parametric Wilcoxon rank-sum test [51] at a 5% significance level [52] to investigate the significant difference between our algorithm results. When P > 0.05 showed that it has significant differences and statistical advantage.…”
Section: Wilcoxon Rank-sum Testmentioning
confidence: 99%